Associations between green/blue spaces and mental health across 18 countries - White, M. P.; Elliott, L. R.; Grellier, J.; Economou, T.; Bell, S.; Bratman, G. N.; Cirach, M.; Gascon, M.; Lima, M. L.; Lõhmus, M.; Nieuwenhuijsen, M.; Ojala, A.; et al. (Scientific Reports, 2021)
Living near, recreating in, and feeling psychologically connected to, the natural world are all associated with better mental health, but many exposure-related questions remain. Using data from an 18-country survey (n= 16,307) we explored associations between multiple measures of mental health (positive well-being, mental distress, depression/anxiety medication use) and: (a) exposures (residential/recreational visits) to diferent natural settings (green/inland-blue/coastalblue spaces); and (b) nature connectedness, across season and country. People who lived in greener/ coastal neighbourhoods reported higher positive well-being, but this association largely disappeared when recreational visits were controlled for. Frequency of recreational visits to green, inland-blue, and coastal-blue spaces in the last 4 weeks were all positively associated with positive well-being and negatively associated with mental distress. Associations with green space visits were relatively consistent across seasons and countries but associations with blue space visits showed greater heterogeneity. Nature connectedness was also positively associated with positive well-being and negatively associated with mental distress and was, along with green space visits, associated with a lower likelihood of using medication for depression. By contrast inland-blue space visits were associated with a greater likelihood of using anxiety medication. Results highlight the benefts of multi-exposure, multi-response, multi-country studies in exploring complexity in nature-health associations.